2001
DOI: 10.1111/j.1746-1561.2001.tb06490.x
|View full text |Cite
|
Sign up to set email alerts
|

A School‐Community Partnership for At‐Risk Students in Pennsylvania

Abstract: This four-year, school-community health improvement project addressed fragmentation and under-utilization of services of an at risk population in a county in central Pennsylvania. A population profile was developed that included demographic, attitudinal, and behavioral information as well as information related to liabilities and assets that affect resiliency and decrease or increase the likelihood of academic success. The profile was used in the planning and implementation of risk-reduction strategies that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Literature on school programs suggests that lasting improvements in children's behavior and academic achievement are better achieved through a combined school and social approach that is based on children's developmental needs, and that introduces skills that provide alternate ways to cope with difficult and emotionally charged situations [30][31][32]. This four-pronged approach takes into account all of the factors that the current study found influential in adolescents' beliefs about violence and aggression-school attachment, parental supervision, teacher support, community support, and a holistic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on school programs suggests that lasting improvements in children's behavior and academic achievement are better achieved through a combined school and social approach that is based on children's developmental needs, and that introduces skills that provide alternate ways to cope with difficult and emotionally charged situations [30][31][32]. This four-pronged approach takes into account all of the factors that the current study found influential in adolescents' beliefs about violence and aggression-school attachment, parental supervision, teacher support, community support, and a holistic approach.…”
Section: Discussionmentioning
confidence: 99%
“…For example, basic tenants of African American tradition and values place heavy emphasis on interactional and oral methods of transmitting information (Bradley-Johnson & Dean, 2000;Diala et al, 2000), yet time constraints on doctor visits make it unlikely that ADHD education will be provided in this manner through the health care sector. Future studies should explore the potential roles of the medical sector, the school system, and public education campaigns in devising culturally relevant ADHD education methods (Austin & Husted, 1998;McMahon, Browning, & Rose-Colley, 2001).…”
Section: Cultural Variations In Adhd Knowledge Perceptions and Cues To Actionmentioning
confidence: 99%